The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.cgh.2013.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Reduced Plasma 25-Hydroxy Vitamin D and Increased Risk of Cancer in Patients With Inflammatory Bowel Diseases

Abstract: Background & Aims Vitamin D deficiency is common among patients with inflammatory bowel diseases (IBD) (Crohn’s disease or ulcerative colitis). The effects of low plasma 25-hydroxy vitamin D (25[OH]D) on outcomes other than bone health are understudied in patients with IBD. We examined the association between plasma level of 25(OH)D and risk of cancers in patients with IBD. Methods From a multi-institutional cohort of patients with IBD, we identified those with at least 1 measurement of plasma 25(OH)D. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(68 citation statements)
references
References 34 publications
(46 reference statements)
1
67
0
Order By: Relevance
“…In concordance, both the National Geriatric Society and International Osteoporosis Foundation recommend maintaining serum 25(OH)D .30 ng/mL, a concentration at which parathyroid hormone concentrations begin to plateau in relation to 25(OH)D (39)(40)(41). Although these categorical recommendations for defining vitamin D deficiency and sufficiency are mainly based on investigations focused on bone metabolism, most studies to our knowledge that have examined patients with IBD have used a similar definition of a 25(OH)D concentration ,20 ng/mL to represent vitamin D deficiency (12,14,31,(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…In concordance, both the National Geriatric Society and International Osteoporosis Foundation recommend maintaining serum 25(OH)D .30 ng/mL, a concentration at which parathyroid hormone concentrations begin to plateau in relation to 25(OH)D (39)(40)(41). Although these categorical recommendations for defining vitamin D deficiency and sufficiency are mainly based on investigations focused on bone metabolism, most studies to our knowledge that have examined patients with IBD have used a similar definition of a 25(OH)D concentration ,20 ng/mL to represent vitamin D deficiency (12,14,31,(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…102 A review of prospective cohort data on CRC prevention suggested that achieving a 25(OH)D serum concentration of 30-44ng/mL had the greatest benefits. 99 Analysis of the incidence of malignancies in 2 809 IBD patients with a median follow-up of 11 years found that patients with vitamin D deficiency (~33%) were at increased risk of cancer (adjusted OR, 1.82; 95% CI, 1.25-2.65) compared with patients with sufficient vitamin D. 103 Each 1 ng/mL increase in 25(OH)D plasma concentration was associated with an 8% reduction in the risk of CRC.…”
Section: Prevention Of Colorectal Carcinomamentioning
confidence: 99%
“…In patients with vitamin D deficiency, in both CD and UC, the risk of having a flare is about 2-fold increased [41] , whereas substitution in CD was shown to reduce relapse risk in quiescent CD [42] . Moreover, lower vitamin D serum levels were also revealed to be associated with an increased risk of colorectal cancer in IBD patients [43] .…”
Section: Environmental Factors Known To Play a Role For Disease Flaresmentioning
confidence: 99%